Results of an interlaboratory comparison of analytical methods for quantification of anhydrosugars and biosugars in atmospheric aerosol. (October 2017) - Chiara Pietrogrande, M.; Barbaro, Elena; Bove, M. Chiara; Clauser, Giuseppe; Colombi, Cristina; Corbella, Lorenza; Cuccia, Eleonora; Dalla Torre, Stefano; Decesari, Stefano; Fermo, Paola; Gambaro, Andrea; Gianelle, Vorne; et al.
Abstract: An interlaboratory comparison was performed to evaluate the analytical methods for quantification of anhydrosugars – levoglucosan, mannosan, galactosan – and biosugars – arabitol, glucose and mannitol – in atmospheric aerosol. The performance of 10 laboratories in Italy currently involved in such analyses was investigated on twenty-six PM (particulate matter) ambient filters, three synthetic PM filters and three aqueous standard solutions. An acceptable interlaboratory variability was found, determined as the mean relative standard deviation (RSD%) of the results from the participating laboratories, with the mean RSD% values ranging from 25% to 46% and decreasing with increasing sugar concentration. The investigated methods show good accuracy, evaluated as the percentage error (ε%) related to mean values, since method biases ranged within ±20% for most of the analytes measured in the different laboratories. The detailed investigation (ANOVA analysis at p < 0.05) of the contribution of each laboratory to the total variability and the measurement accuracy shows that comparable results are generated by the different methods, despite the great diversity in terms of extraction conditions, chromatographic separation - more recent LC (liquid chromatography) and EC (exchange chromatography) methods compared to more widespread GC (gas chromatography) - and detection systems, namely PAD (pulsed amperometric detection) or mass spectrometry. Graphical abstract: Highlights: An intercomparison study was performed in 10 Italian laboratories for quantifying sugars in PM. Gas and Liquid chromatography and NMR methods were used for analysis of 26 ambient and 3 synthetic PM filters. Different separation and detection systems yielded comparable results for most of the samples. Low interlaboratory variability (RSD% from 25% to 46%) and good accuracy (ε% within ±20%) were found. Abstract : Capsule An interlaboratory study evaluated comparability of common analytical methods used to quantify sugars in ambient aerosol filter samples, as relevant markers of biomass burning and biogenic emissions.